2010
DOI: 10.1271/bbb.100358
|View full text |Cite
|
Sign up to set email alerts
|

Flower Color Modification by Engineering of the Flavonoid Biosynthetic Pathway: Practical Perspectives

Abstract: The status quo of flavonoid biosynthesis as it relates to flower color is reviewed together with a success in modifying flower color by genetic engineering. Flavonoids and their colored class compounds, anthocyanins, are major contributors to flower color. Many plant species synthesize limited kinds of flavonoids, and thus exhibit a limited range of flower color. Since genes regulating flavonoid biosynthesis are available, it is possible to alter flower color by overexpressing heterologous genes and/or down re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 63 publications
0
121
0
6
Order By: Relevance
“…From the point of view of biotechnology application, as the loss of the newly acquired traits in subsequent generations or under certain environmental conditions has been reported elsewhere [6] [31] [32], the next important task is to ensure the reliability and stability of phenotypes reported here after several generations of propagation. Furthermore, it is very important to breed transgenic petunia plant carrying both SRYAS1 and SRY4'-CGT by crossing experiment, which is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of biotechnology application, as the loss of the newly acquired traits in subsequent generations or under certain environmental conditions has been reported elsewhere [6] [31] [32], the next important task is to ensure the reliability and stability of phenotypes reported here after several generations of propagation. Furthermore, it is very important to breed transgenic petunia plant carrying both SRYAS1 and SRY4'-CGT by crossing experiment, which is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…In horticulture, color conversion of flower pigments has become possible based on new findings of anthocyanin research. Creation of flowers in new colors enriches our life; for example, the creation of blue roses is a noteworthy achievement (Tanaka et al, 2010). Genetic engineering is the key technology for converting flower color, and it became possible after the discovery of genes involved in anthocyanin biosynthesis and elucidation of their expression mechanisms.…”
mentioning
confidence: 99%
“…Next, tetrahydroxychalcone is stereospecifically isomerized by CHI to colorless flavanone, which is catalyzed further to colorless dihydroquercetin by flavanone 3-hydroxylase (F3H) and flavonoid 3'-hydroxylase (F3'H). Dihydroquercetin is catalyzed in turn by DFR, ANS, and UFGT3 to form an anthocyanin (cyanidin-3-glucoside), thereby generating the red color of the labella [5,6]. In contrast to a previous study [8] We also identified several DEGs that encode key enzymes regulating carotenoid synthesis in petals and labella, such as phytoene synthase (PSY), phenylalanine ammonialyase (PAL), and phytoene desaturase (PDS).…”
Section: Genes Related To Floral Differentiationmentioning
confidence: 74%
“…Of these, anthocyanins are the major contributors to flower color [6]. A class of water-soluble flavonoids, anthocyanins are synthesized in the cytosol and localized in vacuoles.…”
Section: Introductionmentioning
confidence: 99%